The Effectiveness of Using Comic-Based Worksheet as Fiqh Learning Media for Junior High School Student - Defika Andriana Sari; Zakariyah (Journal of Research in Islamic Education, 2023)
This article aims to describe the effectiveness of using comic-based student worksheets with fiqh material as learning media. The modern era has had a big impact on the systematic way of life in society. This change was driven by the development of science and technology in it, which was very influential, especially in education. Currently in making learning media not only use objects that can be searched around life but can also be digital. Student worksheets are teaching materials that can be developed in making fiqh learning media. In carrying out this research, using a type of quasi-experimental research as well as a literature review method that analyzes fiqh teaching materials in the form of comic-based student worksheets. The data is described based on the results of research on the effectiveness of using student worksheets that have been done with previous researchers. The results show that the use of comic-based teaching materials can increase effectiveness in the learning process with fiqh material, giving a significant influence and interest of students in teaching and learning activities on the understanding and clarity of fiqh material